Business Analysis Techniques : 99 Essential Tools for Success. - Cadle, James (BCS Learning & Development Limited, 2014)
The role of the business analyst is to formulate options for a way forward and produce business cases setting out conclusions and recommendations. This professional discipline requires the widest possible array of tools and the ability to use each when and where it is needed. The new edition provides 99 possible techniques and applies them within a framework of stages. It complements Business Analysis (ed Debra Paul, Donald Yeates and James Cadle), also published by BCS, and offers a more detailed description of the techniques used in business analysis, together with practical advice on their application. This book will be of enormous benefit to business analysts, managers and to students of information systems and business strategy.
Keywords: Business planning.; Organizational effectiveness.; elektronické knihy; electronic books